2014
DOI: 10.1088/1757-899x/63/1/012121
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation resistance of a nanostructured 316 austenitic stainless steel

Abstract: High strength state of UFG steel produced by severe plastic deformation N A Enikeev, X Sauvage, M M Abramova et al. -Effect of high pressure torsion on the aging kinetics of -titanium Ti-15Mo alloy Svetlana Gatina, Irina Semenova, Milos Janecek et al. Abstract. The reduction of grain size down to several tens or hundreds of nanometers leads to the enhancement of radiation resistance of metals. Based on this approach, the aim of the Labex EMC3 (Energy Materials and Clean Combustion Center) project "Naninox" is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 8 publications
0
7
0
1
Order By: Relevance
“…Theoretical studies on nanomaterials by Bai et al [41] indicate an increased defect accumulation in the matrix with decreased boundary density. Rajan et al [42] also suggested that there is a depletion of vacancies due to grain boundaries that act as defect sinks resulting in a decreased bubble density in nanostructured austenitic stainless steel under He ion irradiation. The shorter distance to the surface in a NP facilitates the annihilation of vacancies via the ingress of interstitials without the need for the vacancy to migrate all the way to the sink as suggested by the modelling work of [31].…”
Section: Resultsmentioning
confidence: 99%
“…Theoretical studies on nanomaterials by Bai et al [41] indicate an increased defect accumulation in the matrix with decreased boundary density. Rajan et al [42] also suggested that there is a depletion of vacancies due to grain boundaries that act as defect sinks resulting in a decreased bubble density in nanostructured austenitic stainless steel under He ion irradiation. The shorter distance to the surface in a NP facilitates the annihilation of vacancies via the ingress of interstitials without the need for the vacancy to migrate all the way to the sink as suggested by the modelling work of [31].…”
Section: Resultsmentioning
confidence: 99%
“…In metallic materials, maximum nanoscale depth can reach up to 0.2 microns, which is beneficial for assessing the mechanical properties of thin films and coatings [ 20 , 21 , 22 ]. On the other hand, nIIT has been successfully utilized, with specific reference to SS 316L, to inspect the effects of surface modifications, such as those induced by irradiation [ 23 ], pulsed plasma [ 24 ], nitriding [ 25 ], sol-gel thin coating [ 26 ], and more. To the best of the authors’ knowledge, no studies, except for the one published by [ 27 ] on the fatigue behavior of PBF-LB SS 316L under different orientations (vertically, horizontally and at a 45° angle) using Vickers instrumented macro-indentation, have been conducted on the elastoplastic behavior of either SS 316L steel or its PBF-LB counterpart.…”
Section: Introductionmentioning
confidence: 99%
“…sprin ger. com/ journ al/ 40195. irradiation [11,12]. Interfaces between oxide inclusions and the matrix were also shown to act as effective defect sinks in oxide-dispersion-strengthened (ODS) steels [13,14].…”
Section: Introductionmentioning
confidence: 99%